Advances in quantum chemistry. Volume 32, Quantum Systems in Chemistry and Physics. Part II - Wilson, S. (Stephen), 1950-; ScienceDirect eBooks (San Diego : Academic Press, 1999)
The description of quantum systems is fundamental to an understanding of many problems in chemistry and physics. This volume records a representative slection of the papers delivered at the second European Workshop on Quantum Systems in Chemistry and Physics which was held at Jesus College, Oxford, April 6-9, 1997. The purpose of this international Workshop was to bring together chemists and physicists with a common interest--the quantum mechanical many-body problem--and to encourage collaboration and exchange of ideas on the fundamentals by promoting innovative theory and conceptual de.
Chapter 14. Systematic Sequences of Even-Tempered Gaussian Primitives for Diatomic Molecules in Solution: A Preliminary Study Using Continuum Solvation ModelsChapter 15. Beyond the Transition State Treatment; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Quantum chemistry; Quantum theory; SCIENCE -- Chemistry -- Physical & Theoretical; Quantum chemistry; Quantum theory; Electronic books